A rare presentation of Potassium Iodate toxicity. (August 2017) - Ershad, Muhammed; Kodumayil, Ashid; Alessai, Galal S
Abstract : Introduction: Potassium Iodate is a compound used for nutritional supplementation in table salt and administered to individuals exposed to radioactive iodine. Toxicity to Potassium Iodate is not a common presentation to the emergency room. In this case report, we present a young man who was brought to the ED after deliberate oral ingestion of Potassium Iodate, who then had a remarkable clinical course in the hospital. Case description: A 26-year-old Sri Lankan male was referred to the Emergency department as a case of ST elevation MI from the primary health centre, where he had presented with diarrhoea. In the Emergency, he admitted to have consumed a "handful" of potassium iodate powder, 17 hours prior to presentation to ED, as an act of deliberate self-harm. He then had complains of cramping abdominal pain, loose stools and vomiting. He was also complaining of visual disturbances, in the form of seeing everything with a greyish tinge. On initial assessment of patient, he was talking, with a patent airway, had no evidence of any respiratory distress and had stable haemodynamics and GCS of 14/15. Visual acuity was 6/6 but stated everything appears grey. ECG showed ST elevation and tall T waves in chest leads, reciprocal changes of ST depression in III, aVF with prolonged PR and QRS interval. Echocardiogram was done which showed no regional wall motion abnormality. Labs showed high potassium (K-7.6meq/L). Other notable results were CPK of 3909U/L, myoglobin more than 5000ng/ml, high sensitive Troponin T - 220ng/L, Troponin I - 1.8ng/L, Leukocytosis of 34500/uL with neutrophilia, creatinine - 226umol/L, BUN - 6.07mmol/L, Sodium - 139meq/L, mixed respiratory and metabolic acidosis with normal anion gap and osmolar gap. Fibreoptic laryngoscopy looking for any features of corrosive damage to upper airway proved normal. Over few hours he developed methhaemoglobenaemia. Treatment was started for hyperkalemia but only had transient response to repeated medical management. Emergency hemodialysis was started to treat the hyperkalaemia. He was later admitted under the intensive care with input from renal team. He received hemodialysis for more than 3 weeks. He was also found to have only light perception in both eyes with bilateral vitreous hemorrhage and posterior vitreous detachment. Patient as of date has started to pass urine. He is off hemodialysis. He still has renal failure and is continuing treatment in the medical floor. Conclusion: Though renal failure, hyperkalemia and retinopathy have been described in literature, the presentation and clinical course of this patient were unique in many ways including severe rhabdomyolysis leading to acute tubular necrosis and bilateral vitreous hemorrhage with posterior vitreous detachment.